County Over Party: How Governors Prioritized Geography Not Particularism in the Distribution of Opportunity Zones. Issue 4 (18th October 2022) - Glick, David; Palmer, Maxwell
Abstract : Allocating resources is a central function of government, and the distributive politics literature provides considerable evidence of leaders around the world directing resources to co-partisan voters and officials. In the United States, studies of 'presidential particularism' have recently demonstrated strategic targeting by the federal executive branch. This letter extends the inquiry to states using an unusually rich case in which all governors simultaneously faced decisions about allocating a constrained resource – tax advantaged status for economic development – from an exogenously generated list of geographic possibilities. This study tests whether governors rewarded their supporters' and allies' areas alongside two alternatives: (1) spreading the wealth by geographic subunits and (2) policy need. It finds no evidence of gubernatorial particularism. Instead, Republicans and Democratic governors prioritized allocating opportunity zones geographically and made efforts to designate at least one in each county. They were also responsive to policy need.